Odpowiedź :
[tex]metoda\ przeciwnych\ wspolczynnikow:\\\\\begin{cases} \frac{1}{2 }x - 3y= -12\ \ |*2\\ 4x - \frac{1}{3}y= -25\ \ |*3 \end{cases}\\\\\begin{cases} x - 6y= -24\ \ \ |*(-12)\\ 12x - y= -75 \end{cases}\\\\\begin{cases} -12x +72y=288 \\ 12x - y= -75 \end{cases}\\+--------\\71y=213\ \ |:71\\y=3\\\\ x - 6y= -24\\x-6*3=-24\\x-18=-24\\x=-24+18\\x=-6\\\\\begin{cases}x=-6\\y=3 \end{cases}[/tex]
[tex]metoda\ podstawiania:\\\\\begin{cases} x - 6y= -24 \\ 12x - y= -75 \end{cases} \\\\\begin{cases} x=6y -24 \\ 12 (6y-24) - y= -75 \end{cases}\\\\\begin{cases} x=6y -24 \\ 72y-288- y= -75 \end{cases}\\\\\begin{cases} x=6y -24 \\ 71y = -75+288 \end{cases}\\\\\begin{cases} x=6y -24 \\ 71y = 213\ \ :71\end{cases}[/tex]
[tex]\begin{cases} x=6*3 -24 \\ y =3\end{cases} \\\begin{cases} x=-6 \\ y =3\end{cases}[/tex]